Stambiosios pramonės atsiradimas Klaipėdos krašte (XIX amžiaus pabaiga - XX amžiaus pradžia) - Žukas, Julius (Lietuvos istorijos studijos, 2007)
Industrialization in Germany in the 19th century was not a homogeneous process. Firstly, the industrial upheaval started and quickly permeated into the West German lands. The rail freight and the system of factories based on heavy mechanical production and hired labor started and developed there. Meanwhile, the provinces of Prussia were rather poor, even at the end of the 19th century. Talking at this point, the most behindhand was the province of East Prussia. That slippage was mainly conditioned by poor natural resources, adverse geopolitical situation, financial deficiency, undeveloped infrastructure, and other important factors. The investment was impeded by the unsafe frontier with the Russian Empire, the major German trade sets could not find any serious interests there, whereas the province bourgeoisie was too conservative and tried to avoid any novelty.  One of the most sequestered and the least modernized districts of the province was Klaipėda Region (Memelland), mostly determined by the specific historical development of the city of Klaipėda, which left the seaport located in a very convenient spot, yet without any natural economical rearward. Consequently, the development of the city was rather slow (Klaipėda had only 17,490 inhabitants in 1861), and there were no other important trading centers in the region. The entire economics of Klaipėda substantially depended on the opportunity to intercede in trading between Russia and other European countries. However, those opportunities were constricted because of the rivalry with Königsberg, which was the center of East Prussia, and the protectionist politics of the Russian Empire. The Russian governance was developing Liepāja (Libau) port in the latter part of the 19th century, thus nurturing another strong contestant to Klaipėda. Therefore, the trading set of Klaipėda's Region was not able to hoard up a large capital and hesitated to invest in modern branches of economics. The enterprisers of other regions of Germany established almost all of the first major industrial corporations of Klaipėda.  Oddly enough, the mining company laid the foundations for the heavy industry in the region of scarce resources. The corporation named Stantien & Becker used industrial methods to mine amber from the bottom of the Curonian Lagoon near Juodkrantė (Schwarzort) from 1862 until 1891. The company wrung 2250 tons of amber during that period. Throughout the working years, it was the biggest company in the land of East Prussia. The amber was realized in Southeast Europe and Asia.  Union, the factory of chemical production that manufactured artificial fertilizers, was another big industrial company in Klaipėda's region. The fabrication required a great deal of stock, and a fair amount of it was transported from Spain, USA, and even Australia.  At the end of the 19th century, two more great industrial companies were established - the corporation of wood manufacturing and the cellulose factory. The latter one soon became the biggest company in the region. The factory produced more than thirty thousand tons of cellulose per year, before World War I, and the greatest part of the production was realized in foreign countries.